External debt problem of Vietnam and its determinants - Le, Kieu Oanh (2009)
Since Doi Moi reforms in 1986, Vietnam observed rapid economic growth and was recognized as one of the fastest developing economy in the world. However, the country experienced persistent current account deficit financed by external borrowings. This paper seeks to uncover external debt determinants of Vietnam. We examined the impact of macroeconomic variables, such as gross national savings, domestic investment, effective exchange rates, and relative price ratio on the current account balance. A pooled regression based on savings-investment and elasticity approaches was also performed, taking into account Vietnam’s major trading partners and the remarkable trading events such as the signing of ASEAN Free Trade Area (AFTA) and Vietnam-United States Bilateral Trade Agreement. Our findings show that the public sector was the main determinant of the external debt due to low public saving rates as a result of fiscal deficits, and high public investments in socio-economic development projects.